Malassezia versus Candida in Healthy Dogs - Sihelská Z.; Pangrácová Piterová M.; Čonková E.; Harčárová M.; Böhmová E. (Folia Veterinaria, 2017)
The genera Malassezia and Candida include yeasts which are members of the normal mycobiota of the skin and mucosal sites of humans and other warm-blooded animals. These yeasts are associated with a variety of dermatological disorders and also systemic diseases in humans and other animals. This study confirms the occurrence of Malassezia and Candida species in healthy dogs. Samples were collected from different body sites: external ear canal, interdigital area, skin of the axilla and of the neck, and the oral and rectal mucosae. The isolates were identified using phenotypic methods (biochemical-physiological and morphological characteristics). The presence of yeasts were investigated in the specimens from 70 healthy dogs. Malassezia species were isolated in 44 dogs from which 84 Malassezia isolates were obtained. Only one Candida isolate was obtained from the dogs examined. It was found that Candida does not occur in dogs normally and Malassezia was the main colonizing yeast in healthy dogs.